THE EFFECT OF MIND MAPPING LEARNING TECHNIQUE ON THE STUDENTS’ INTEREST AND LEARNING OUTCOMES ON EXCRETORY SYSTEM AT GRADE XI SCIENCE OF MAN 1 MEDAN - Putri, Amalia (Jurnal Pelita Pendidikan, 2024)
This research aims to determine the effect of mind mapping learning techniques on the interest and learning outcomes of students in class XI MIPA at MAN 1 Medan. This research is a quantitative research using quasi-experimental research type. This study used two classes, namely experimental classes using mind mapping learning techniques and control classes using conventional learning techniques. Student interest in learning was obtained through a questionnaire sheet of student interest in learning with indicators of feelings of pleasure, student interest, student attention, and student involvement. Student learning outcomes were obtained through multiple choice objective tests. The learning outcome test was used to assess students' abilities at the C1-C6 cognitive level. The results of hypothesis testing were obtained using independent samples t-test. The results showed that there was an effect of mind mapping technique on students' interest and learning outcomes with a significance value of 0.003 for students' interest and 0.000 for students' learning outcomes.